KEADILAN DISTRIBUTIF, KEADILAN PROSEDURAL, KEADILAN INTERAKSIONAL KOMPENSASI DAN KOMITMEN KARYAWAN - R. Philipus Lewis (Jurnal Riset Manajemen dan Bisnis, 2013)
The purpose of this study is to examine the effect of distributive justice, procedural justice, and interactional justice of compensation on employees’ commitment. Primary data have been collected from 53 consultant companies’ employees. Multiple regression is used for testing three hypotheses. The results show that compensation distributive justice and interactional justice have effect on employees’ commitment, while compensation procedural justice show no such effect. Keywords: distributive justice, procederal justice, interactional justice, employees’ commitment